English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solving Equations and use the quadratic formula to solve the equation.
1. 4xsquared - 13x + 3=0
any help?

2007-03-29 14:59:50 · 3 answers · asked by Mark s 1 in Science & Mathematics Mathematics

3 answers

1)

4x^2 - 13x + 3 = 0

One method of solving this is using the "ac" method. For
ax^2 + bx + c = 0, first multiply a and c. a = 4, c = 3, so
ac = 12.

Next, find two factors of 12 which add up to the middle coefficient, -13. The answer to that is -12 and -1.

Now, split -13x into -12x and -x (as per what was just said).

4x^2 - 12x - x + 3 = 0

Here's where we group each pair of terms.

4x(x - 3) - (x - 3) = 0

Factor (x - 3) out of this,

(x - 3)(4x - 1) = 0

Therefore, x = {3, 1/4}

2007-03-29 15:08:36 · answer #1 · answered by Puggy 7 · 1 0

The quadratic formula is:

x = [- b ± √(b² - 4ac)] / 2a

Remember, "a" is the coefficient of the first term. "b" is the coefficient of the second term and "c" is the constant. Just plug those values into the formula directly from your equation and calculate the answer.

x = {- (-13) ± √[(-13)² - 4 (4)(3)]} / 2(4)

This particular equation is also factorable:

(4x - 1)(x - 3) = 0.

Set each factor equal to 0 and then solve.

2007-03-29 22:16:08 · answer #2 · answered by MathBioMajor 7 · 0 0

The answer is (2xsquared+8x)(2xsquared-5x).

2007-03-29 22:10:49 · answer #3 · answered by AB the Baby 2 · 0 0

fedest.com, questions and answers